Outcomes of type 1 diabetes mellitus in pregnancy; effect of excessive gestational weight gain and hyperglycaemia on fetal growth. Issue 1 (January 2019) - Bashir, Mohammed; Naem, Emad; Taha, Faten; Konje, Justin C.; Abou-Samra, Abdul-Badie
Abstract: Aims: To study pregnancy outcomes in patients with type 1 diabetes mellitus (T1DM) and the factors associated with poor outcomes. Methods: A retrospective study of 110 patients with T2DM who attended our diabetes in pregnancy clinic at the Women's Wellness and Research centre, Doha, between March 2015 and December 2016 and 1419 normoglycaemic controls. Results: There was no difference in age, weight, and BMI between the two groups. The incidence of macrosomia, shoulder dystocia and stillbirth were similar in the two groups while that of pre-term labour, pre-eclampsia, Caesarean section (CS), large for gestational age (LGA), neonatal ICU (NICU) admission and neonatal hypoglycaemia were significantly higher in the T1DM than in the control group. From a multivariate regression analysis, excessive gestational weight gain was associated with increased risk of LGA (OR 4.53; 95% CI [1.42–14.25]). Last trimester HBA1c was associated with increased risk for macrosomia [OR 2.46, 95% CI [1.03–5.86)]; LGA [ OR 3.25, 95% CI [1.65–6.40)]; increased risk for C-section (OR 1.96, 95% CI [1.12–3.45]), and increased risk of NICU admission (OR 2.46, 95% CI [1.04–5.86]). The changes in HBA1C between the first and last trimester HBA1c was associated with a reduction in the risk of LGA [OR 0.46, 95% CI [(0.28–0.75)] Conclusion: T1DM in pregnancy is associated with adverse pregnancy outcomes compared to the general population. Reducing gestational weight gain and improving glycaemic control might improve pregnancy outcomes.